pH-sensitive cationic guar gum/poly (acrylic acid) polyelectrolyte hydrogels: Swelling and in vitro drug release - Huang, Yihong; Yu, Huiqun; Xiao, Chaobo (Carbohydrate polymers, 2007)
Novel polyelectrolyte hydrogels (coded as GA) based on cationic guar gum (CGG) and acrylic acid monomer by photoinitiated free-radical polymerization were synthesized with various feed compositions. Fourier transform infrared spectra (FTIR), scanning electron microscopy (SEM), and differential scanning calorimetry (DSC) confirmed that the formation of the polyelectrolyte hydrogels was attributed to the strong electrostatic interaction between cationic groups in CGG and anionic groups in poly (acrylic acid) (PAA). Swelling experiments provided important information on drug diffusion properties, which indicated the GA hydrogels were highly sensitive to pH environments. Potential applications of the hydrogels matrices in controlled drug delivery were also examined. The ketoprofen-loaded CGG/PAA matrices were prepared by hydrogels and directly compressed tablets, respectively. Release behavior of ketoprofen relied on the preparative methods of matrices, ratios of CGG/AA and pH environments. The release mechanism was studied by fitting experimental data to a model equation and calculating the corresponding parameters. The result showed that the kinetics of drug release from the hydrogels in pH 7.4 buffer solution was mainly non-Fickian diffusion. However, for tablets, the drug release in pH 7.4 buffer solution was mainly affected by polymer erosion. The pH of the dissolution medium appeared to have a strong effect on the drug transport mechanism. At more basic pH values, Case II transport was observed, indicating a drug release mechanism highly influenced by macromolecular chain relaxation. The ketoprofen release is also tested in the conditions chosen to simulate gastrointestinal tract conditions. The results implied that the GA hydrogels can be exploited as potential carriers for colon-specific drug delivery.